Agukng magicality in balala' ritual: civic culture of the dayak kanayatn community as a form of preventing the spread of covid-19 - Christanto Syam; Yudhistira Oscar Olendo; Zakarias Aria Widyatama Putra (Jurnal Pendidikan PKN (Pancasila dan Kewarganegaraan), 2023)
The purpose of this research was to know the agukng magicity in Balala' ritual of Dayak Kanayatnese. Agukng in Balala' ritual have rhythm elements, mean and value, and could be seen in symbolic mean. The method for research agukng in Balala’ ritual was qualitative form.The source of data collection were agukng sound and the attitude of Balala' ritual practicioner and submitted with observation technique, interviews, and documentary study. The research findings showed that Balala' ritual have rhythm elements, which were beat and accent that summarized in one rhythm pattern. From symbolic mean, agukng showed bravery symbol, hope, and happiness for the success of Balala' ritual. Agukng in Balala' ritual or lockdown was implemented to resist or prevent pandemic virus COVID19 or known as Corona virus that functioned as connecting communication media between people and Awa Pama or ancestor. With this, agukng in the balala' ritual implicitly conveys an attitude that is worth togetherness in the Dayak Kanayatn community so that they consciously and jointly build a better civilization